The Legal Structure of the Kurdistan Exploration and Production Company (KEPCO) -Analytical Comparative Study - Ahmed, Awara Azad; Sediq, Arez Mohammed (Sulaimani Journal for Humanities, 2021)
Like other oil rich countries, Kurdistan Exploration and Production Company (KEPCO) is one of the state-owned companies (run by Kurdistan Regional Government), along three others, to be established as according to Oil and Gas Law No. 22 of 2007 which is operating and managing oil sector in Iraqi Kurdistan Region. These companies have a great role in developing oil sector, especially KEPCO with is designated to work in exploration and producing oil in the region and other parts of Iraq. In the absence of other state-owned companies in the region, KEPCO and others are considered a new form of companies in the region. The worthiness and legal framework of KEPCO is the subject of this paper. While having this sort of companies in the region is considered an ultimate benefit and leverage for the region, the current applicable regulation in the region have many loopholes and do not answer or address upcoming questions. Therefore, it is recommended to issue another law in the region same as Iraqi Federal law no. 4 of 2018 to include all necessary rules regarding establishment, organization, capital and assets, and converting ownership of the company from state into a publicly held company. In doing so, the experience of Iraq (federal government) and other oil rich countries such as Saudi Arabia can be taken into scrutiny.